Reactive oxygen species reduce myofibrillar Ca(2+) sensitivity in fatiguing mouse skeletal muscle at 37°C - Moopanar, Terence R (Blackwell Science Inc, 2005)
The mechanisms of muscle fatigue were studied in small muscle bundles and single fibres isolated from the flexor digitorum brevis of the mouse. Fatigue caused by repeated isometric tetani was accelerated at body temperature (37°C) when compared to room temperature (22°C). The membrane-permeant reactive oxygen species (ROS) scavenger, Tiron (5 mm), had no effect on the rate of fatigue at 22°C but slowed the rate of fatigue at 37°C to that observed at 22°C. Single fibres were microinjected with indo-1 to measure intracellular calcium. In the accelerated fatigue at 37°C the tetanic [Ca(2+)]i did not change significantly and the decline of maximum Ca(2+)-activated force was similar to that observed at 22°C. The cause of the greater rate of fatigue at 37°C was a large fall in myofibrillar Ca(2+) sensitivity. In the presence of Tiron, the large fall in Ca(2+) sensitivity was abolished and the usual decline in tetanic [Ca(2+)]i was observed. This study confirms the importance of ROS in fatigue at 37°C and shows that the mechanism of action of ROS is a decline in myofibrillar Ca(2+) sensitivity.